(untitled) (Research, Society and Development, 2022)
This work aims to obtain and characterize a spray-dried product (SDP) from an extractive solution of Cinnamomum zeylanicum leaves, to produce a talc for feet. Initially, the influence of the amount of drug, solvent and extractive method were verified, through factorial design (22), evaluating as responses the total flavonoid content (TFC), dry residue (DR) and extraction efficiency (EE). In the drying operation the following conditions were studied: inlet temperature and proportion of adjuvants. Three talc formulations containing cinnamon PES were also obtained and evaluated for Carr’s Index (CI), Hausner Factor (HF), Angle of Repose (AR) and Moisture. According to the results, negative influence was observed using 5 g drug in relation to TFT (-1.02) and EE (-44.14), whereas the solvent ethanol (100%) showed positive influence on the responses, with better content. As for the extraction method, turbolysis showed positive responses for TFT (+2.03), RS (+3.21) and EE (+1.36), being chosen for the other experiments. In the drying operation, the best results were evidenced when 10% adjuvant and inlet temperature of 100 °C were used in relation to TFT and technological properties (CI, FH and AR). Finally, the determination of excipients and their proportions in the formulation presented satisfactory values for moisture and technological properties. The methodologies employed presented important results to produce a talc for feet based on SDP from C. zeylanicum, however further studies are needed to ensure the safety and efficacy of the finished product.